THE ROLE OF MAQASHID SYARIAH INTERPRETATION IN ADDRESSING THE LIMITATIONS OF TRADITIONAL ISLAMIC FAMILY LAW FOR ACHIEVING GENDER-RESPONSIVE AND CHILD-PROTECTIVE LEGAL REFORMS - Anisa, Lina Nur (Institut Agama Islam Ngawi, 2025)
Family law reform in Islam is an urgent necessity in response to social dynamics and contemporary demands for justice. This article aims to analyze the role of maqashid syariah as a normative foundation and practical instrument in the process of reforming Islamic family law. Through qualitative library research, the study reviews various classical and modern literatures as well as empirical studies highlighting the importance of a dynamic and contextual interpretation of maqashid to enable Islamic family law to adapt to social changes without losing the core values of sharia. The findings show that maqashid syariah provides a holistic framework to ensure the protection of women’s, children’s, and other family members’ rights fairly, creating an inclusive and responsive legal system. Major challenges include social resistance, differences in madhhab interpretations, and limited capacity of legal apparatus, requiring educational strategies and constructive dialogue. This article recommends strengthening maqashid-based legal education, harmonizing interpretations, and institutional reforms as crucial steps to realize just and sustainable family law reform in Islam. Thus, maqashid syariah serves as a bridge between tradition and modernity, facilitating the renewal of Islamic family law relevant to the needs of the Muslim community in the era of globalization.